Analisis Teknis dan Ekonomis Penerapan Lampu Penerangan Jalan Umum Panel Surya di Kota Sukabumi - Dion Sanaha; Irzaman Irzaman; Sri Mulatsih (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Abstract. Public Street Light (PSL) with Solar Cell Power has good prospects to be developed in the equator. PSL design must provide reliable service. The aims of this research are to know how the design of PSL with Solar Cell Power can provide a reliable service of The PSL. Besides that, monitoring of the performance of PSL is expected to be carried out centrally, this is to facilitate employees in observing the performance of the lights, also to anticipate damage PSL components. The design of PSL are expected to meet these expectations. This PSL designed can provide data on the performance of the main components of the PSL with Solar Cell Power, namely: Solar Cell, Batteries and LEDs. Economic analysis is taken into account of the design of this PSL. Net Present Value (NPV) are used in analyzing the Smart Design of PSL, which is by adding up all cash flow and investment costs.